21st Century Teachers' Problems: Teachers' Difficulties In Implementing Technology In The Learning Process - Khairani, Muthia; Burhanudin, Burhanudin; Febriani, Afifah; Az-zahra, Dwi Wahyuni (Khalaqa: Journal of Education and Learning, 2025)
Technological developments in the digital era have brought significant changes to the world of education. 21st-century teachers are required to integrate technology into the learning process to create interactive and relevant learning. However, many teachers still face obstacles in implementing technology, such as limited digital skills, lack of institutional support, and limited facilities and time. This study aims to examine the factors causing teachers' difficulties in implementing technology and possible solutions. Interviews with an elementary school teacher revealed that limited facilities and the habit of conventional methods are the main obstacles. Therefore, ongoing training, adequate infrastructure, and support from all parties are needed to improve teacher competency in facing the challenges of 21st-century learning.